Association between coarse particulate matter (PM10-2.5) and nasopharyngeal carcinoma among Taiwanese men. (16th October 2019) - Huang, Hsu-Chih; Tantoh, Disline Manli; Hsu, Shu-Yi; Nfor, Oswald Ndi; Frank, Cheau-Feng Lin; Lung, Chia-Chi; Ho, Chien-Chang; Chen, Chih-Yi; Liaw, Yung-Po
Abstract : The nasopharyngeal tract traps mainly coarse particles in inhaled air. Soluble carcinogenic compounds, endotoxins, and trace metals contained in these particles are potential causes of inflammation and oxidative stress which could enhance carcinogenesis. The aim of this study was to determine the association between coarse particulate matter (PM10-2.5 ) and nasopharyngeal cancer (NPC). A total of 521, 098 men (355 cases and 520, 743 non-cases), aged ≥40 years were included in this study. Data were retrieved from the Taiwan Cancer Registry, the Adult Preventive Medical Services Database, and the Air Quality Monitoring Database. PM10-2.5 was significantly associated with a higher risk of NPC after adjusting for SO2, NOx, O3, age, body mass index, smoking, alcohol drinking, betel nut chewing, exercise, hypertension, diabetes, and hyperlipidemia. With PM10-2.5 <20.44 μg/m 3 as the reference, the ORs and 95% CIs were 1.47; 1.03–2.11, 1.34; 0.94–1.91, and 1.68; 1.16–2.44 for 20.44≤PM10-2.5 <24.08, 24.08≤PM10-2.5 <29.27, and PM10-2.5 ≥29.27 μg/m 3, respectively. PM10-2.5 remained significantly associated with a higher risk of NPC after further adjustments were made for the aforementioned covariates and PM2.5 . The ORs; 95% CIs were 1.42; 0.96 to 2.12, 1.41; 0.94 to 2.10, and 1.71; 1.10 to 2.66 for 20.44≤PM10-2.5 <24.08, 24.08≤PM10-2.5 <29.27, and PM10-2.5 ≥29.27 μg/m 3, respectively. In conclusion, PM10-2.5 was significantly associated with a higher risk of NPC in Taiwanese men.